Answer:
4
Explanation:
the nth term of a geometric sequence is
= a₁
![r^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/h7f8wtyws2qfjuf66o6tzexwulvsc5z6or.png)
where a₁ is the first term and r the common ratio
here a₁ = 2 and r =
=
= 2
then
a₂₈ = 2
![(2)^(27)](https://img.qammunity.org/2023/formulas/mathematics/high-school/69pspqq5jb8acvyte194uu0mns0odydcbm.png)
a₂₆ = 2
![(2)^(25)](https://img.qammunity.org/2023/formulas/mathematics/high-school/6xjxdgt9p3hjmx1e10g9uw6evrftkuejxe.png)
using the rule of exponents
=
, then
![(a_(28) )/(a_(26) )](https://img.qammunity.org/2023/formulas/mathematics/high-school/2q57ndulx1opw8dd7un3kc5m802jew38gx.png)
=
( cancel 2 on numerator/ denominator )
=
![(2^(27) )/(2^(25) )](https://img.qammunity.org/2023/formulas/mathematics/high-school/gnhww2cnxwfw21ig9wkwvsdq7sdpdek1nw.png)
=
![2^((27-25))](https://img.qammunity.org/2023/formulas/mathematics/high-school/mscv2jx1yfv8jyjdt7ebhda2q7t2z9r9sz.png)
= 2²
= 4